DASAR-DASAR PENDIDIKAN ANAK DALAM SURAH LUQMAN - Muhammad Yusuf (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The results of this study displayed that there are some principles of education that cover the main points of religious guidance such as Aqidah, worship, morality and the command to be patient. Those principles are absolute requirement for success after life. Thus, Luqman Al-Hakim educated his children, and also gave a guidance to anyone who wants to trace the path of virtue, which applies to all nations and people in the world. In a nutshell, this purpose has the same way with the Qur'an's mission which is intended to be a blessing for all nature through educational activities. In closing, the Qur'an wishes for the realization of human beings who are built up their full potential, physical, mental and intellectual, so that, the whole human beings are happy in the world and also the hereafter.